2022
DOI: 10.3390/w14091357
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Diazinon on the Survival, Blood Parameters, Gills, and Liver of Grass Carp (Ctenopharyngodon idella Valenciennes, 1844; Teleostei: Cyprinidae)

Abstract: Diazinon (DZN) is a widely used pesticide that can affect the vital organs of non-target aquatic animals—mainly fish. This study evaluated the acute toxicity (LC50) of six DZN concentrations (0.5, 0.75, 1.5, 2, 2.5, and 3 mg·L−1) and, based on its evaluation after 24 h, 48 h, 72 h, and 96 h, two sublethal concentrations for chronic toxicity testing (0.01 and 0.05 mg·L−1) for 21 days of exposure to DZN on grass carp fingerlings (Ctenopharyngodon idella Valenciennes, 1844). The median lethal concentrations of DZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Diazinon is an insecticide widely used to control pests in agriculture, on livestock farms, and in residential areas. However, its use has led to contamination of surface waters in many parts of the world, including the United States [ 1 , 2 , 3 ]. Studies have found traces of diazinon in streams, rivers, and lakes due to runoff from agricultural and residential areas [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Diazinon is an insecticide widely used to control pests in agriculture, on livestock farms, and in residential areas. However, its use has led to contamination of surface waters in many parts of the world, including the United States [ 1 , 2 , 3 ]. Studies have found traces of diazinon in streams, rivers, and lakes due to runoff from agricultural and residential areas [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The insecticide chlorpyrifos is found in agricultural, industrial, and home waste and is considered a primary source of aquatic contamination [ 14 , 15 ]. Nutrient recycling in paddy soils is also threatened by disrupting interactions between micro- and macro-organisms [ 16 , 17 , 18 , 19 , 20 ]. The mangrove habitat is particularly vulnerable to agricultural effluents, mainly because of its location at the river’s mouth.…”
Section: Introductionmentioning
confidence: 99%
“…Cytopathological indicators are crucial for monitoring and evaluating the toxicity of aquatic ecosystems [20][21][22][23][24][25][26]. Prolonged exposure to toxic agents often does not cause death directly; however, the structure and function of vital organs are affected, jeopardizing the individual population.…”
Section: Introductionmentioning
confidence: 99%